Pendeteksian Kerusakan Printer menggunakan Metode Forward Chaining - Amriana Amriana; Albrecht Yordanus Erwin Dodu; Pebri Ramadhan Mas (ILKOM Jurnal Ilmiah, 2020)
As technology advances, almost everyone has a printer in their home as a printing aid. but not a few printers that have small or big problems. with this technological advancement, almost all people have personal smarthpones. This research aims to build a moble based system where users can solve printer problems by using applications on their smartphones based on knowledge obtained from experts created by the Forward Chaining method. This expert system can detect nine different types of printers owned by Canon manufacturers with total of 26 Problem and 38 symptomps and has an 80 % of accuracy.